PENGARUH MEDIA LAGU TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SMA SANTUN UNTAN PONTIANAK - Siahaan, Friscila; Hairida, Hairida; Sahputra, Rachmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by low motivation and student learning outcomes in chemistry learning. The purpose of this study is to determine the differences in motivation, learning outcomes in grade X SMA Santun Untan Pontianak students as well as determining the influence of learning using media songs to motivation and learning outcomes in compound nomenclature material. Sampling technique is done by saturated sampling, class X A as control class and class X B as experiment class. The research used quasi experimental design with experimental design design in this research is nonequivalent control group design. Data collection techniques used are measurement techniques, and communication. Data collection tool used test result of learning in the form of pretest and postest matter of nomenclature of compound and nontes in the form of motivation questionnaire. Based on the results of the motivation questionnaire analysis using two-tailed Two-Tail Test (? = 5%) obtained Sig (P-value) of 0.503 and analysis of learning outcomes of the gain value data using the Paired T-test ( Paired-Samplest Test) (? = 5%) obtained Sig (P-value) of 0.386. This shows that there is no difference in motivation and learning outcomes of students who are given learning using the media with the songs students are given the conventional learning. Calculation effect size (ES) motivation obtained results of -0.33 and learning results obtained ES value of -0.39 which means no effect on motivation and learning outcomes of students of grade X SMA Santun Untan Pontianak. Keywords: Media Song, Motivation, Learning Result, Compound nomenclature.